Weakly Nonlocal Supersymmetric KdV Hierarchy - Miškinis, P. (Nonlinear Analysis: Modelling and Control, 2005)
The present work offers a weakly nonlocal generalization of superKdV, which possesses also an unlimited number of conservation laws and exact solutions.
Keywords: nonlinear evolution equation; integrable systems; KdV equation; supersymmetry; nonlocality